KAJIAN RASIO BUBUR SALAK (Salacca edulis) DENGAN BUBUR WORTEL (Daucus carota L.) TERHADAP SIFAT KIMIA DAN ORGANOLEPTIK SIRUP SALAK - Muhammad Faisal; Suwati; Syirril Ihromi; Hutasoit Hutasoit (The Journal of Teknologi Pangan, 2022)
Snake fruit is a tropical fruit that is spread throughout Southeast Asia, specifically Indonesia, and can be used as an ingredient in drinks. In making syrup, the raw materials used usually consist of only one type of fresh fruit, so it is necessary to combine it with other ingredients to improve the nutritional content of the resulting syrup, such as adding carrots. The purpose of this study was to determine the effect of adding snake fruit puree, carrots, and sugar on reducing sugar levels, beta-carotene levels, and the organoleptic properties of snake fruit syrup. This study used a CRD (completely randomized design) with treatment of two factors, namely factor I, consisting of four levels: W1 = without comparison of carrot pulp (100% snake fruit puree), W2 = 90% snake fruit puree + 10% carrot puree, W3 = 80% snake fruit puree + 20% carrot puree, and W4 = 70% snake fruit puree + 30% carrot puree. While factor II consisted of 2 levels, namely, G1 = 25% sugar concentration and G2 = 50% sugar concentration, in order to obtain eight treatment combinations Each treatment was repeated twice to obtain 16 experimental units. Parameter analysis carried out included reducing sugar levels, beta-carotene levels, color, aroma, and taste. Observational data were analyzed using analysis of variance at a significant level of 5%. If the treatment is significantly different, then it will be further tested using the Honest Significant Difference (HSD) test at the same level. Combining snake fruit puree and carrots with sugar concentration had a significant effect on the color and aroma of snake fruit syrup, but lowering sugar levels, beta-carotene levels, and taste tests had no effect. The W2G2 treatment (450 g of snake fruit puree and 50 g of carrot puree) and 50% sugar concentration gave the best results in the organoleptic test of snake fruit syrup.